Fatigue of materials III : advances and emergences in understanding : proceedings of the third biennial symposium : sponsored by the Minerals, Metals & Materials Society (TMS) and ASM International held during Materials Science & Technology 2014 (MS & T'14), October 12-16, 2014 in Pittsburgh, Pennsylvania - Materials Science & Technology Conference (2012 : Pittsburgh, Pa.); Srivatsan, T. S.; Imam, M. Ashraf; Srinivasan, Raghavan (Hoboken : Wiley, 2014)
This volume contains papers presented in the third international symposium titled Fatigue of Materials: Advances and Emergences in Understanding held during the Materials Science and Technology 2014 meeting in Pittsburgh, Pennsylvania, USA, in October 2014. The book contains contributions from engineers, technologists, and scientists from academia, research laboratories, and industries. The 19 papers are divided into five topical areas: Session 1: Aluminum Alloys Session 2: Ferrous Materials I Session 3: Ferrous Materials II Session 4: Composite Materials Sess.
Aluminum -- Advanced materials -- Composites -- Ferrous materials -- Modeling.
Includes indexes.
Print version record.
Keywords: Materials -- Fatigue -- Congresses; Materials -- Fatigue; Electronic books; Conference papers and proceedings